Analisis Penggunaan Media Ultrasi Terhadap Hasil Belajar Matematika Siswa Kelas 3 di SDN Inpres Pucuke - Fitriani, Nurul; Nurwalidainismawati, Tri Supriyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics is a subject that is often considered difficult and boring. The reason is that teachers deliver material only focusing on theory or problem solving without a contextual approach, the lack of variation in learning methods such as the use of educational media or games so that students are less interested in mathematics subjects. To maintain the effectiveness of learning, teachers can use learning media during KBM (Teaching and Learning Activities). Learning media can be used to increase learning motivation and activate student responses, so that students' ability to solve problems increases. This study aims to analyze the effect of using Ultrasi media on mathematics learning outcomes of 3rd grade students at SDN Inpres Pucuke. This study uses a quasiexperimental and mixed method approach. The research sample consisted of 17 3rd grade students of SDN Inpres Pucuke. Data were obtained through pre-test and post-test and even involved observation and interviews. The results of the study showed a significant increase in students' average scores from 63.52 in the pretest to 89.70 in the posttest. With an average mean difference of 26.18 points. The t-test showed significant results (p